Penerapan Model Pembelajaran Kolaboratif Dalam Pembelajaran PPKn Kelas Xi Di SMK Ma’arif Sukawening - Fadila, Azmi Nur Izza; Dikarsa, Asep Anggi (JURNAL MANAJEMEN PENDIDIKAN, 2026)
Application of Collaborative Learning Model in Class XI PPKN Learning at Smk Ma'arif SukaweningThis research aims to investigate the role of the collaborative learning approach in enhancing students’ critical thinking abilities in Civics Education (PPKn) at SMK Ma’arif Sukawening. A quasi-experimental method with a Nonequivalent Control Group design was utilized, measuring students’ critical thinking through pretest and posttest assessments encompassing analysis, evaluation, and drawing conclusions. The application of collaborative learning was monitored through the stages of planning, implementation, and assessment, involving group discussions, Think-Pair-Share techniques, and group inquiry exercises. The results reveal that students in the experimental group showed a more substantial improvement in critical thinking compared to those in the control group, as evidenced by higher N-Gain values and statistically significant differences in posttest scores. Collaborative learning promoted active engagement, the exchange of ideas, and collective problem-solving, allowing students to advance their reasoning skills more systematically. These findings validate the efficacy of collaborative learning in fostering higher-order thinking skills among vocational students in Civics Education.